First successful birth of twins in India following the transfer of vitrified oocytes - Priya Selvaraj; Kamala Selvaraj; Kalaichelvi Srinivasan (Wolters Kluwer Medknow Publications, 2010)
We report the first twin pregnancy and birth in India after the transfer of embryos generated from vitrified and thawed oocytes to a 41-year-old woman who was in a donor program. Embryos were generated from the microinjection of pre-prepared sperms into vitrified oocytes. Twin male babies weighing 750 and 860 g were born by emergency cesarean section. Vitrification is one of the most promising options in cryopreservation and preservation of embryos and oocytes.